4
$\begingroup$

This is derived from my answer to $\sum_{m=0}^{\infty}x^m\sum_{k=0}^{\infty}W_{m,k}f_k=\sum_{n=1}^{\infty}\frac{1}{n(n+1)}\sum_{k=0}^{\infty}\left(\frac{n+x}{n(n+1)}\right)^k f_k$?

For $n, m \ge 0, n+m\ge 2$, what is the value of $W_{m, n} =\sum_{k=1}^{\infty} \frac{1}{(k+1)^mk^{n}} $.

My results:

  • From the definition \begin{align*} W_{0, n} &= \zeta(n) \\ W_{m, 0} &= \zeta(m)-1 \text{.} \end{align*}

  • Recurrence from which everything else follows: $$ W_{m, n} = W_{m-1, n}-W_{m, n-1} \text{.} $$

  • Explicit values: \begin{align*} W_{1, n} &= \sum_{k=0}^{n-2} (-1)^k\zeta(n-k) + (-1)^{n-1} \\ W_{m, 1} &=-\sum_{k=0}^{n-2} \zeta(n-k) + m \text{.} \end{align*}

I have not yet worked out the general formula for $W_{m,n}$.

$\endgroup$
3
  • 1
    $\begingroup$ Sorry to be pedantic: Is there a question here? Is it, "What is the formula for general $W_{m,n}$?" $\endgroup$ – Eric Towers May 18 '18 at 2:54
  • 1
    $\begingroup$ I have a related question at math.stackexchange.com/questions/2783981/… where I've identified the coeffecients as having a Mellin transform inverse pair, I've also got a paper in progress at github.com/crowlogic/a/blob/master/… there is some already known stuff about it at linas.org/math/gkw.pdf as well. It is derived from the transfer operator of the Lüroth series map which you can read about at the link above $\endgroup$ – crow May 18 '18 at 2:55
  • $\begingroup$ Yep, that is the same question, aside from the binomial coefficient. I didn't see an explicit formula for the coefficients, though $\endgroup$ – marty cohen May 18 '18 at 4:55
2
$\begingroup$

The eigenvalues are given by \begin{equation} \begin{array}{cl} \lambda_m & = W_{m, m}\\ & = \sum_{n = 1}^{\infty} \frac{1}{n^{m + 1} (n + 1)^{m + 1}}\\ & = \sum_{n = 0}^{\frac{m}{2} + \frac{1}{4} - \frac{(- 1)^m}{4}} \zeta (2 n) \frac{2 (- 1)^{m + 1 - 2 n} \Gamma (2 m - 2 n + 2)}{\Gamma (m + 2 - 2 n) \Gamma (m + 1)} \end{array} \end{equation} where \begin{equation} \frac{m}{2} + \frac{1}{4} - \frac{(- 1)^m}{4} = [0, 1, 1, 2, 2, 3, 3, 4, 4, 5, \ldots] {where} m = 0, 1, 2, \ldots, 9, \ldots \end{equation} This form of the function means that $Y_{m, n, k} = 0$ when $k$ is odd and $m = n$ so that \begin{equation} Y_{m, m, k} = \left\{ \begin{array}{ll} 0 & k {is} {odd}\\ \frac{2 (- 1)^{m + 1 - k} \Gamma (2 m - k + 2)}{\Gamma (m + 2 - k) \Gamma (m + 1)} & k {is} {even} \end{array} \right. \end{equation} when $m \neq n$ the off-diagonals involve also odd-integer values of $\zeta$ so we need to find a general expression for $Y_{m, n, k}$ and not just the diagonals $Y_{m, m, k}$ where

$$\begin{array}{ll} W_{m, n} & = \binom{n}{m} \sum_{k = 1}^{\infty} \frac{1}{(k + 1)^{n + 1} k^{m + 1}}\\ & = \binom{n}{m} \sum_{k = 0}^{\max (m, n) + 1} \zeta (k) Y_{m, n, k} \end{array}$$

also

\begin{equation} Y_{m, n, 0} = \frac{2 (- 1)^{m + n + 1} \Gamma (m + n + 2)}{(n + 1) \Gamma (m + 1)^2 \Gamma (n + 1 - m)} = - \frac{2}{\Gamma (m)^2} \prod_{k = 1}^{2 n - 1} (- 1)^{n - 1} \left\{ \begin{array}{ll} 1 & k = m\\ n - m + k & k \neq m \end{array} \right. \label{Y0} \end{equation} so that \begin{equation} \begin{array}{lfl} \hat{y}_{n, 0} (s) & = \sum_{m = 0}^n \frac{Y_{m, n, 0}}{m + s}\\ & = \sum_{m = 0}^n \frac{\frac{2 (- 1)^{m + n + 1} \Gamma (m + n + 2)}{(n + 1) \Gamma (m + 1)^2 \Gamma (n + 1 - m)}}{m + s}\\ & = \mathit{} - 2 \hspace{0.17em} \frac{(- 1)^n_{} 3F2 \left[ \begin{array}{c} \begin{array}{lllll} s & & - n & & n + 2 \end{array}\\ \begin{array}{lll} 1 & & s + 1 \end{array} \end{array} ; \hspace{0.17em} 1 \right]}{s} \end{array} \end{equation}

where 3F2 is a generalized hypergeometric function and

\begin{equation} Y_{m, n, 1} = 0 \label{Y1} \end{equation} and \begin{equation} Y_{m, n, 2} = 0^{m + n} + \frac{(- 1)^{m + n} \Gamma (n + m)}{\Gamma (m + 1)^2 \Gamma (n - m)} \label{Y2} \end{equation} and the coeffecients of $\zeta (3)$ are simply related to a shifted version of the coeffecients of $\zeta (2)$ \begin{equation} Y_{m, n, 3} = Y_{m, n - 1, 2} \label{Y3} \end{equation}

$\begin{array}{ll} Y_{m, n, 4} & = {Res} (\hat{y}_{n, 4} (s), s = - m)\\ & = \lim_{s = - m} (s + m) \hat{y}_{n, 4} (s)\\ & = {Res} (\hat{y}_{n, 4} (s), s = - m)\\ & = \left\{ \begin{array}{ll} 0 & n \leqslant 2\\ \frac{(- 1)^{m + n + 1}}{(m!^{})^2} \left( \prod_{k = 0}^{m - 1} (n - k) \right) \left( \prod_{k = 1}^{m - 2} (n + k) \right) (n^2 - (m + 1) n + m (m - 1)) & n \geqslant 3 \end{array} \right. \end{array}$

we also have

$Y_{m, n, 5} = \frac{(- 1)^{1 + n - m} \left( m^2 + n^2 - 3 \hspace{0.17em} m + n \right) \prod_{k = 1}^{2 \hspace{0.17em} m - 2} (k + 1 + n - m)}{(m!)^2}$

if we write the polynomials specifying the coefficients as hyper-geometric functions we find

\begin{equation} \begin{array}{ll} y_{n, 0} (x) & = 2 \hspace{0.17em} (- 1)^{n + 1}_{} 2F1 (0 - n, n + 2 ; \hspace{0.17em} 1 ; \hspace{0.17em} x)\\ y_{n, 1} (x) & = 0\\ y_{n, 2} (x) & = \hspace{0.17em} (- 1)^n_{} 2F1 (n, 1 - n ; \hspace{0.17em} 1 ; \hspace{0.17em} x)\\ y_{n, 3} (x) & = (- 1)^{n + 1} 2F1 (n - 1, 2 - n ; 1 ; x)\\ y_{n, 4} (x) & = (- 1)^n 4F3 \left( \begin{array}{l} \begin{array}{lll} {}[0 - n] & [n - 1] & \left[ \frac{1}{2} - \frac{n}{2} \pm \frac{1}{2} \hspace{0.17em} \sqrt{- 3 \hspace{0.17em} n^2 + 6 \hspace{0.17em} n + 1} \right] \end{array}\\ \begin{array}{ll} {}[1] & \left[ - \frac{1}{2} - \frac{n}{2} \pm \frac{1}{2} \hspace{0.17em} \sqrt{- 3 \hspace{0.17em} n^2 + 6 \hspace{0.17em} n + 1} \right] \end{array} \end{array} ; x \right)\\ y_{n, 5} (x) & = (- 1)^{n + 1}_{} 4F3 \left( \begin{array}{l} \begin{array}{lll} {}[n] & [- n - 1] & \left[ - \frac{1}{2} \pm \frac{1}{2} \hspace{0.17em} \sqrt{- 4 \hspace{0.17em} n^2 - 4 \hspace{0.17em} n + 9} \right] \end{array}\\ \begin{array}{ll} {}[1] & \left[ - \frac{3}{2} \pm \frac{1}{2} \hspace{0.17em} \sqrt{- 4 \hspace{0.17em} n^2 - 4 \hspace{0.17em} n + 9} \right] \end{array} \end{array} ; x \right) \end{array} \end{equation} where $[a \pm b]$ is actually two elements, $[a + b]$ and $[a - b]$

$\endgroup$
3
  • $\begingroup$ Very impressive. You have certainly taken this much further than I could. Accepted. $\endgroup$ – marty cohen May 18 '18 at 5:31
  • $\begingroup$ Thanks. It would be nice to know the entire formula $\endgroup$ – crow May 18 '18 at 13:43
  • 1
    $\begingroup$ You might find the related question at math.stackexchange.com/questions/2787558/… interesting $\endgroup$ – crow May 19 '18 at 21:41
2
$\begingroup$

Just to be complete, here is everything I have got so far, including two recurrences at the end that don't seem to be of much use.

According to Wolfy,

$ W_{1,1} =1\\ W_{1,2} =\dfrac{\pi^2}{6}-1\\ W_{2, 1} =2-\dfrac{\pi^2}{6}\\ W_{2, 2} =\dfrac{\pi^2}{3}-3\\ W_{1, 3} =\zeta(3)+1-\dfrac{\pi^2}{6}\\ W_{3, 1} =-\zeta(3)-\dfrac{\pi^2}{6}+3\\ W_{2, 3} =\zeta(3)+4-\dfrac{\pi^2}{2}\\ W_{3,2} =\zeta(3)+\dfrac{\pi^2}{2}-6\\ W_{3, 3} =10-\pi^2\\ $

$W_{0, n} =\zeta(n) $.

$W_{m, 0} =\zeta(m)-1 $.

$\begin{array}\\ W_{m+1, n+1} &=\sum_{k=1}^{\infty} \frac{1}{(k+1)^{m+1}k^{n+1}}\\ &=\sum_{k=1}^{\infty} \frac{1}{(k+1)k(k+1)^mk^{n}}\\ &=\sum_{k=1}^{\infty} \frac{1}{(k+1)^mk^{n}}(\frac1{k}-\frac1{k+1})\\ &=\sum_{k=1}^{\infty} \frac{1}{(k+1)^mk^{n+1}}-\sum_{k=1}^{\infty} \frac{1}{(k+1)^{m+1}k^{n}}\\ &=W_{m, n+1}-W_{m+1, n}\\ \end{array} $

or $W_{m, n} =W_{m-1, n}-W_{m, n-1} $.

$m=0$:

$W_{1, n+1}\\ =W_{0, n+1}-W_{1, n}\\ =\zeta(n+1)-W_{1, n}\\ =\zeta(n+1)-\zeta(n)+W_{1, n-1}\\ =...\pm\zeta(2)\mp 1\\ $

so $W_{1,n} =\sum_{k=0}^{n-2} (-1)^k\zeta(n-k) +(-1)^{n-1} $.

$n=0$:

$W_{m+1, 1}\\ =W_{m, 1}-W_{m+1, 0}\\ =W_{m, 1}-\zeta(m+1)+1\\ =-\zeta(m+1)+1+W_{m, 1}\\ =-\zeta(m+1)-\zeta(m)+2+W_{m-1, 1}\\ =...-\zeta(2)+m-1+W_{1, 1}\\ $

so $W_{m, 1} =-\sum_{k=0}^{n-2} \zeta(n-k) +m $.

Check:

$(3, 3)\\ =(2, 3)-(3, 2)\\ =((1, 3)-(2,2))-((2,2)-(3, 1))\\ =(1, 3)-2(2, 2)+(3, 1)\\ =(z(3)-z(2)+1)-2((1, 2)-(2, 1))+(-z(3)-z(2)+3)\\ =-2z(2)+4)-2((1, 2)-(2, 1))\\ =-2z(2)+4)-2(z(2)-1-(-z(2)+2)\\ =-6z(2)+10\\ =-\pi^2+10\\ $

$\begin{array}\\ W_{m, n}-\zeta(m+n) &=\sum_{k=1}^{\infty} (\frac{1}{(k+1)^mk^{n}}-\frac1{k^{m+n}})\\ &=\sum_{k=1}^{\infty} \frac1{k^n}(\frac{1}{(k+1)^m}-\frac1{k^{m}})\\ &=-\sum_{k=1}^{\infty} \frac1{k^n}(\frac{(k+1)^m-k^m}{(k+1)^mk^{m}})\\ &=-\sum_{k=1}^{\infty} \frac1{(k+1)^mk^{m+n}}\sum_{j=0}^{m-1}\binom{m}{j}k^j\\ &=-\sum_{j=0}^{m-1}\binom{m}{j}\sum_{k=1}^{\infty} \frac1{(k+1)^mk^{m+n-j}}\\ &=-\sum_{j=0}^{m-1}\binom{m}{j}W_{m, m+n-j}\\ \end{array} $

so, isolating the $j=0$ term,

$W_{m, m+n}\\ =\zeta(m+n)-W_{m, n}-\sum_{j=1}^{m-1}\binom{m}{j}W_{m, m+n-j}\\ =\zeta(m+n)-W_{m, n}-\sum_{j=1}^{m-1}\binom{m}{j}W_{m, n+j}\\ =\zeta(m+n)-\sum_{j=0}^{m-1}\binom{m}{j}W_{m, n+j} $.

Similarly, for $n$

$\begin{array}\\ W_{m, n}-\zeta(n) &=\sum_{k=1}^{\infty} (\frac{1}{(k+1)^mk^{n}}-\frac1{k^{n}})\\ &=\sum_{k=1}^{\infty} \frac1{k^n}(\frac{1}{(k+1)^m}-1)\\ &=-\sum_{k=1}^{\infty} \frac1{k^n}(\frac{(k+1)^m-1}{(k+1)^m})\\ &=-\sum_{k=1}^{\infty} \frac1{(k+1)^mk^{n}}\sum_{j=1}^{m}\binom{m}{j}k^j\\ &=-\sum_{j=1}^{m}\binom{m}{j}\sum_{k=1}^{\infty} \frac1{(k+1)^mk^{n-j}}\\ &=-\sum_{j=1}^{m}\binom{m}{j}W_{m, n-j}\\ \end{array} $

so that $W_{m, n} =\zeta(n)-\sum_{j=1}^{m}\binom{m}{j}W_{m, n-j} $.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.